Analysis of the Relationship between Sharia Investment and Macroeconomic Growth: An Empirical Study in Indonesia - Ahmad Muqorrobin; Adi Putra; Yunie Rahayu (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze the relationship between Islamic investment and macroeconomic growth in Indonesia using a qualitative approach through an exploratory descriptive design. Data were collected through in-depth interviews with academics, Islamic finance practitioners, regulators, and economic observers, supplemented by documentation studies from various official sources such as the Financial Services Authority (OJK), Statistics Indonesia (BPS), and Bank Indonesia. The results indicate that Islamic investment contributes positively to driving macroeconomic growth, particularly through financing the real sector and infrastructure development supported by sovereign sukuk instruments. The application of Islamic principles based on ethics, fairness, and the prohibition of usury contributes to creating a sustainable and inclusive investment ecosystem. Islamic investment also has a multiplier effect on the economy by strengthening MSMEs, creating jobs, and improving public welfare. However, the development of Islamic investment still faces several challenges, such as low levels of public literacy regarding Islamic finance, limited investment product variety, and the need for regulations that are more adaptive to global market dynamics. Therefore, closer synergy is needed between the government, regulators, industry players, and academics to strengthen the sharia investment ecosystem and optimize its role in inclusive and sustainable national economic development.